A Policy Analysis of the Development of Elite Swimming in China Between 2000 and 2012: A National Team Perspective. Issue 12 (13th August 2017) - Zheng, Jinming
Abstract: A variety of factors have contributed to China's recent recovery in elite swimming in particular its success in the London Olympiad. The poor performance at the 2000 Sydney Olympic Games was a 'wake-up call', which in conjunction with Beijing's successful Olympic bid in 2001, opened policy windows prompting large-scale review and reform from which a broad range of 'heavyweight' policy actions were introduced and implemented. However, the road to recent success has been 'bumpy' during which there were other key events that have left an indelible imprint on Chinese swimming. Therefore, the multiple streams framework in general and the concept of policy windows in particular afford a theoretical gateway to structure policy analysis of elite swimming in China. Moreover, as a Western-derived theory the application of which to a sports context has been very sporadic, the multiple streams framework is evaluated regarding its applicability, or 'compatibility'. Five semi-structured interviews with key stakeholders were conducted, accompanied by comprehensive document analysis of official documents and website information of associated sports-governing bodies and associations, and influential domestic and foreign media.